Falling Kingdoms - Book 1 - Rhodes, Morgan (New York : Razorbill, 2012)
"A fantasy about three kingdoms on the brink of war and the destiny of one princess"--Provided by publisher.
Accelerated Reader
Keywords: Princesses; Juvenile fiction; Princesses; Fiction; Fantasy; Kings, queens, rulers, etc; Fiction; Kings, queens, rulers, etc; Fiction; Fantasy